Studi Sosiologi Agama terhadap Konflik Otoritas Agama dan Adat dalam Tradisi Ararem di Biak - Buiney, Vinda; Pinotoan, Denni; Lahamendu, Natalia; Wibowo, Markus (Program Studi Sosiologi Agama Fakultas Ushuluddin, Adab dan Dakwah IAIN Manado, 2024)
This study aims to analyze the authority conflict between religion and tradition in the Ararem tradition in Biak society.Religion and tradition, as two influential normative systems, often complement each other, but in this case, a clash arises when tradition, through the Ararem tradition, dominates marriage, while the church advocates for holy matrimony. The large dowry requirement in the Ararem tradition hinders holy matrimony, causing tension between the two authorities.Using a qualitative approach and religious sociology study through the theory of authority conflict, this research reveals the dynamics of the relationship between religion and tradition and its impact on the social life of the Biak community.The study uses interviews, observations, and documentation to gather data, which is then analyzed to provide a deeperunderstanding of the imbalance between religion and tradition in marriage practices. The research was conducted in Biak Numfor, Papua.